ANALISIS PROSEDUR KLAIM BPJS DAN SOP RAWAT INAP GUNA MENUNJANG EFEKTIVITAS KERJA PEGAWAI DI PMN RUMAH SAKIT MATA CICENDO BANDUNG: ANALYSIS OF BPJS CLAIM PROCEDURES AND INPATIENT SOPS TO SUPPORT EMPLOYEE EFFECTIVENESS AT PMN CICENDO EYE HOSPITAL BANDUNG - Sigit Gustiana; Feby Wahyuni Savitri (JURNAL TERAS KESEHATAN, 2022)
The purpose of this research is about BPJS Claim Procedures and Inpatient SOP to Support Employee Work Effectiveness at PMN Cicendo Eye Hospital Bandung. This study used qualitative research methods. The type of research is descriptive while the data collection techniques used are observation, interviews, and literature study. This type of research was chosen because it is in accordance with the problems studied. In general, BPJS claims at PMN Cicendo Eye Hospital Bandung are in accordance with established procedures. However, there are several obstacles in collecting claim files, such as a diagnosis letter that is left behind by the doctor's signature, the completeness of the introductory file and incomplete examination results. For inpatient admissions, it is quite good in providing services immediately, in patient admission procedures, in accordance with what has been determined in correct and appropriate services. Acceptance of new patients is a major part of the treatment process before carrying out an examination to determine the next action to perform surgery or to go home from the hospital.